2016
DOI: 10.3171/2015.1.jns142066
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the subthalamic nucleus for deep brain stimulation

Abstract: F uture progress to refine targets for deep brain stimulation (DBS) is critically dependent on precise placement and verification of electrodes in the brain. No stereotactic target is of more clinical importance or more nuanced regarding its imaging than the subthalamic nucleus (STN). The STN is difficult to image because of its biconvex shape, small size, oblique spatial orientation in 3 planes, and its close proximity to the substantia nigra (SN).3 A high level of accuracy is required as the motor region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 58 publications
0
68
0
4
Order By: Relevance
“…8)(140). Therefore, QSM is an ideal technique to accurately and precisely guide electrode placement in DBS treatment for advanced PD patients and other patients with tremor and dystonia (140,141). Current promising results strongly argue in favor of additional clinical evaluations across multiple DBS centers to evaluate whether the inclusion of QSM in presurgical MRI (rather than current T2w protocols) can overall improve health outcomes in PD patients undergoing DBS.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…8)(140). Therefore, QSM is an ideal technique to accurately and precisely guide electrode placement in DBS treatment for advanced PD patients and other patients with tremor and dystonia (140,141). Current promising results strongly argue in favor of additional clinical evaluations across multiple DBS centers to evaluate whether the inclusion of QSM in presurgical MRI (rather than current T2w protocols) can overall improve health outcomes in PD patients undergoing DBS.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…Atlas-based indirect targeting or direct targeting of images have also been used at some centers [4, 8, 11, 12]. Each of these methods has its own advantages and disadvantages [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported various methods for image acquisition in preparation for DBS surgery. For some structures, such as the pedunculopontine nucleus, there is no consensus on the optimal target site, and therefore it is even more important to devise and introduce targeting methods [3, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…The second is the direct method, which was developed by the work of Bejjani et al in 2000 [7] in which the STN is directly visualized as a hypointense structure on T2 weighted images. Direct localization became easier with the improvements of magnetic resonance imaging (MRI) sequences and the use of special stereotactic software to perform 3D image reconstruction and help in the calculations [8,9,10,11,12]. Many studies assessed the direct coordinates and compared them to the coordinates obtained by the indirect method [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%